The elements of canonical prescription with particular consideration of Polish canonized civil law - SKONIECZNY, PIOTR (Prawo Kanoniczne, 2014)
The author presents systematically all the elements of “civil” canonical prescription, i.e. not penal, referring them to the canonized Polish civil law. In his commentary he recalls not only the canonical doctrine, but also the civil, presenting in addition the relevant Rotal jurisprudence. He distinguishes, then, the canonical elements of canonical prescription and the canonico-civil elements. He considers to be canonical elements: the object of prescription, title and good faith. He holds to be canonico-civil elements: possession, time, and the way time is calculated. As for this last element, he makes particular reference to the Polish civil code as canonized law. According to the author, the canonical elements correct the undesirable effects that result from the application of the canonico-civil elements. In his opinion, the structure of the elements of canonical prescription is a consequence of the ecclesiological presuppositions of the canonical order.